Aphid–feeding plant bug: A new record of Dicyphus miyamotoi Yasunaga (Hemiptera: Heteroptera: Miridae: Bryocorinae) from the Korean Peninsula - Jung, Sunghoon; Duwal, Ram Keshari; Lee, Seunghwan (Zootaxa, 2012)
The plant bug genus Dicyphus Fieber 1858 (Miridae: Bryocorinae: Dicyphini) is described with more than 70 species (Schuh 2002–2011) and 43 species have been documented in the Palaearctic region (Kerzhner & Josifov 1999). In Fareast Asia, only two species are recognized: D. parkheoni Lee & Kerzhner 1995 from the Korean Peninsula, and D. miyamotoi Yasunaga 2000 from Japan.